A comparative study of morphology and pathogenesis of Cuscuta and Orobanche – the two devastating parasitic plants - KANNAN, C; PATHAK, ADITI (The Indian Journal of Agricultural Sciences, 2016)
Orobanche and Cuscuta are two completely different types of holoparasitic plants that behave as devastating weeds on many economically important crops and pose serious challenges in their management. They are phaneroamic and non-photosynthetic plants which require other host plants for their nutrient requirement. In the present study both Orobanche and Cuscuta were compared in terms of their morphology, anatomy and pathology. The study helps in understanding the differences in the target site of the parasites, viz. leaf and stem for Cuscuta and roots for Orobanche and the difference in their ecology. The seeds of the two parasitic weeds showed morphological differences, viz. in their seed size, coat structure and texture. The conditions for germination of Orobanche was very stringent and followed certain defined sequence in terms of water absorption, pre-conditioning, sensitivity to germination stimulants. However, the germination of Cuscuta was more spontaneous and moisture was the major requirement. Post-germination development of both the parasitic weeds was result of the chemotropic response of the receptors in the parasites to the stimuli from the host. Cuscuta and Orobanche represent different lineages of evolution in their parasitic nature and have different haustorial anatomy. Parasitization of the host was very rapid in Cuscuta (27-31 days) with multiple haustorial connections with the host stem, leaf, petiole, fruits and even on its own stem when compared to Orobanche with mostly single point of entry into the host and about 45-60 days to emerge above ground to produce a floral stalk.